Behavioral Characteristics of Limnoperna fortunei under Different Light Conditions - MA Jun, TAO Ze-yi, WANG Ying-cai, WANG Zhang-peng, LI Tian-cui (长江科学院院报)
[Objective] As an invasive fouling organism, Limnoperna fortunei causes increasingly severe damage to water conservancy projects. To develop new prevention and control methods, this study aims to explore the effects of different light conditions on the behaviors of Limnoperna fortunei. [Methods] The highly active Limnoperna fortunei of different shell lengths were collected from field, acclimated, and then placed in experimental porcelain dishes partially covered with shading plates to create shaded areas. At the beginning of the experiment, the Limnoperna fortunei were exposed to light, and the environmental conditions of different light intensities and different wavelengths of light were established. Four behavioral parameters—shell opening, adhesion, migration, and light avoidance—were used to characterize their responses to light stress, in order to investigate the effects of different light conditions on their behavioral characteristics. [Results] The results of shell opening and adhesion behaviors of Limnoperna fortunei under different light intensities showed that with increasing light intensity, shell opening frequency and material exchange decreased. Strong light inhibited the secretion of byssus and the adhesion behavior of Limnoperna fortunei to a certain extent. Different light colors varied in their effects on byssal adhesion, with white, purple, and red light showing the strongest effects. Specifically, red light at 40 000 lux had the most significant inhibitory effect on byssal adhesion. The results of migration and light avoidance behaviors of Limnoperna fortunei under different light intensities showed that as light intensity increased, migration distance and light avoidance tendency first increased and then decreased. Within the light intensity range of 10 000-20 000 lux, migration distance and light avoidance tendency peaked with increasing light intensity, but reached their minimum at 40 000 lux. The migration distance and light avoidance tendency of Limnoperna fortunei showed similar patterns under different wavelengths of light. Limnoperna fortunei with shell length of 5-10 mm were more affected by light stress and showed higher light avoidance tendency, while those measuring 10-30 mm exhibited greater light tolerance. [Conclusion] In the prevention and control of Limnoperna fortunei, strong light with a light intensity above 40 000 lux can be applied to create unfavorable conditions and reduce their activity. White, purple, and red light with a light intensity of more than 40 000 lux will reduce or affect their adhesion behavior, while light within the range of 10 000-20 000 lux is more effective for expelling Limnoperna fortunei. Although the practical application will be limited by available space, light attenuation, and other factors, light may serve as a simple, fast, effective, low-cost, and environmentally-friendly control method for Limnoperna fortunei.